Enhancing School Health Program Effectiveness: The Strategic Role of Physical Education, Sports, and Health Teachers in Senior High Schools - Haeril Haeril; Mohamd Mbaydeen; Rumiya Almakaeva (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze and describe the role of Physical Education, Sports, and Health teachers in optimizing the implementation of the School Health Program in public senior high schools in Bantul Regency. Methodology: This study employed a survey method involving 31 teachers as the total population. Data were collected using a structured questionnaire based on educational, preventive, curative, and managerial indicators. Instrument validity was confirmed through expert judgment, and reliability was tested using Cronbach’s alpha. Supporting data were obtained through observation and documentation, and analyzed using descriptive percentage techniques. Main Findings: The results indicate that the role of teachers in optimizing is generally at a moderate level. The educational aspect is the most dominant, while the preventive, curative, and managerial aspects are less optimal. implementation tends to be partial, with limited teacher involvement in management and insufficient integration across health program components. Novelty/Originality of this study: This study provides a comprehensive analysis of teachers’ roles by integrating educational, preventive, curative, and managerial aspects within a single framework. It also offers a context-based perspective at the senior high school level, highlighting the strategic position of teachers as key actors in optimizing school health programs.